Hubungan Growth Mindset Dengan Kemampuan Pemecahan Masalah Matematika Siswa Kelas V Sekolah Dasar Kecamatan Senen - Myisha Keilani Bukhari; Yurniwati; Petrus Paulus Mbette Suhendro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the correlation between growth mindset and mathematical problem-solving ability among fifth-grade elementary school students in Senen District, Central Jakarta. This study employed a quantitative correlational design. The population consisted of all fifth-grade students in public elementary schools in Senen District, with a sample of 295 students selected using simple random sampling. Data were collected through a questionnaire and a mathematics problem-solving test and analyzed using descriptive statistics and the Spearman correlation test with SPSS. The results showed a positive and significant correlation between growth mindset and mathematical problem-solving ability (r = 0.529, p < 0.05), indicating a moderate correlation. These findings suggest that students with higher levels of growth mindset tend to have better mathematical problem-solving ability.